PERENCANAAN SISTEM PENGELOLAAN SAMPAH KOTA DEPOK (Studi Kasus: Kecamatan Pancoran Mas Kota Depok, Jawa Barat) - Deni Kurniawan (FT-USNI, 2017)
This research is aim at determining relationship between conscientiousness, agreeableness, neuroticism, openness, and extraversion with citizenship behavior on managing the environment on Depok Jaya citizen. The method used was survey with a correlational study by involving 85 sample. There were six instruments which measured citizenship behavior on managing the environment (reliability 0,932), conscientiousness (reliability 0,943), agreeableness (reliability 0,931), neuroticism (reliability 0,893), openness (reliability 0,914), and extraversion (reliability 0,873). Data has been analyzed by two-way ANOVA. Research results revealed that there is positive and significant correlation among those variables, even though it has been controlled by second-order correlation, it is significant among them. Therefore, it could be concluded that if citizenship behavior on managing the environment would be improved, then citizen conscientiousness, agreeableness, neuroticism, openness, and extraversion should be taken into consideration.